PENGARUH SISTEM PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN DENGAN KOMPETENSI SUMBER DAYA MANUSIA SEBAGAI VARIABEL MODERASI - Fiane Rina Sambuaga (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2020)
This study examines the internal control system of the quality of financial statements with human resource competence as a moderating variable. The study used a survey method using a sample of civil servants in local government organizational units. The sampling method inThis study examines the internal control system of the quality of financial statements with human resource competence as a moderating variable. The study used a survey method using a sample of civil servants in local government organizational units. The sampling method in this study was purposive sampling. The data obtained were analyzed using SPSS 23 and WarpPLS 5.0. The results showed that the internal control system on the elements of the control environment had no effect and had no significant impact on the quality of the financial statements. In contrast, the element of control activities had a positive and significant effect on the quality of the financial statements. However, human resource competencies can moderate the internal control environment on the quality of financial statements. The inverse results found that human resource competencies cannot moderate internal control activities on the quality of financial statements. this study was purposive sampling. The data obtained were analyzed using SPSS 23 and WarpPLS 5.0. The results showed that the internal control system on the elements of the control environment had no effect and had no significant.